Technostress at work during the COVID-19 lockdown phase (2020–2021): a systematic review of the literature - Bahamondes-Rosado, Maria Emilia; Cerdá-Suárez, Luis Manuel; Dodero Ortiz de Zevallos, Gino Félix; Espinosa-Cristia, Juan Felipe (Frontiers in Psychology, 2023)
Technostress is a psychosocial phenomenon associated with the use of technologies to the detriment of health, the same one that during the pandemic was accelerated in the work considering home confinement. This work aims to systematize the main research on the impact of technostress at work during the severe confinement stage of the pandemic, between the years 2020 and 2021, with the purpose of identify and evaluate its main determining factors. A systematic review of the literature was carried out during COVID-19, using the words "technostress work COVID-19". The works found focus mainly on analyzing the creators and inhibitors of technostress in workers, as well as the main consequences of the materialization of this technological risk associated with work performance during the stage of confinement by COVID-19. Techno invasion and techno overload were identified as the main techno stressors, with the main type of technostress appreciated in the literature being techno fatigue. Technostress is identified as a problem that had direct and relevant effects during the season of severe confinement and remote work at home due to COVID-19; highlighting techno fatigue as the most frequent type of stress, and techno stressors such as techno invasion and overload as the ones that presented the highest incidence.